PENDIDIKAN NILAI: KONSEP DAN IMPLEMENTASINYA DALAM DUNIA PENDIDIKAN - Benny Prasetiya; Sofyan Rofi (LPPM STAI Muhammadiyah Probolinggo, 2017)
The formation of values as the core of national education goals is certainly not immediately tangible for granted, but it takes an effort of education in a systematic and well-planned. One form of the government's efforts to achieve national education goals is to organize educational services for all citizens through units of the education as education providers track, level and type of education that is required by law.In this case, the school as an institution (institution) education which is a container where the educational process is done, have a complex and dynamic system. In its activities, the school is a place that is not just a gathering place for students and teachers, but are in the order of the system complex and interrelated. Keywords: education, values